O CÂNONE CRÍTICO-POÉTICO DE MANOEL DE BARROS - de Camargo, Goiandira Ortiz (Organon, 2012)
This study aims to examine the critical-poetic literary canon in Manoelde Barros. The self-reflexivity in Barros’ poetry forms a creative consciousness whicharticulates literary creation and critical invention in the poetic space. In Manoel deBarros’s works, the poems question the crisis of the word and the compositionalprocess which giving form to intentions presented in the author’s essays allows us todepict the poet’s aesthetic project. The choice of a universe of ordinary things, thepreference for that which despised by society, the feeling of fragmentation, the searchof an Adamic word, which denotates a lost language – all this are some of the recurrentmotives that are interwoven to the liric voice of Barros’s poetry. Departing from areshaping of the poetic canon that can be obtained by mean of a critical approach topoetry, we will examine the “critical metaphor” – the precarious condition in whichthe insertion of poetry in the world as metaphor inaugurates the space of criticism ofthe word as well as the criticism of mechanisms used for representation of reality.